2022
DOI: 10.1142/s1793545822430040
|View full text |Cite
|
Sign up to set email alerts
|

Deep-skin third-harmonic generation (THG) imagingin vivoexcited at the 2200 nm window

Abstract: The skin is heterogeneous and exerts strong scattering and aberration onto excitation light in multiphoton microscopy (MPM). Shifting to longer excitation wavelengths may help reduce skin scattering and aberration, potentially enabling larger imaging depths. However, previous demonstrations of skin MPM employ excitation wavelengths only up to the 1700[Formula: see text]nm window, leaving an open question as to whether longer excitation wavelengths are suitable for deep-skin MPM. Here, in order to explore the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Towards this goal, different MPM technologies have been developed: (1) higher order nonlinear three-photon imaging 7,11 can be used to suppress the surface background 1,3 and (2) shiing to longer excitation wavelengths to reduce tissue attenuation and hence increase the multiphoton signal level in deep tissue. 1,7,8,[12][13][14][15] To reduce the excitation light attenuation caused by absorption and scattering, the excitation wavelengths are commonly selected within the following four "tissue optical windows": 2,16-18 NIR-I (800 nm window, 650-950 nm), 16,19 NIR-II (1300 nm window, 1100-1350 nm), 17,20,21 NIR-III (1700 nm window, 1600-1840 nm), 1,17,20 and NIR-IV (2200 nm window, 2100-2300 nm). 7,8,17 These four optical windows have been conrmed by ex vivo transmittance measurement, tissue phantom simulation, and in vivo imaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Towards this goal, different MPM technologies have been developed: (1) higher order nonlinear three-photon imaging 7,11 can be used to suppress the surface background 1,3 and (2) shiing to longer excitation wavelengths to reduce tissue attenuation and hence increase the multiphoton signal level in deep tissue. 1,7,8,[12][13][14][15] To reduce the excitation light attenuation caused by absorption and scattering, the excitation wavelengths are commonly selected within the following four "tissue optical windows": 2,16-18 NIR-I (800 nm window, 650-950 nm), 16,19 NIR-II (1300 nm window, 1100-1350 nm), 17,20,21 NIR-III (1700 nm window, 1600-1840 nm), 1,17,20 and NIR-IV (2200 nm window, 2100-2300 nm). 7,8,17 These four optical windows have been conrmed by ex vivo transmittance measurement, tissue phantom simulation, and in vivo imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Towards this goal, different MPM technologies have been developed: (1) higher order nonlinear three-photon imaging 7,11 can be used to suppress the surface background 1,3 and (2) shifting to longer excitation wavelengths to reduce tissue attenuation and hence increase the multiphoton signal level in deep tissue. 1,7,8,12–15…”
Section: Introductionmentioning
confidence: 99%
“…In terms of wavelength selection in MPM of biological tissues, the ideal optical window should have low scattering and absorption. For deep tissue imaging, the following four optical windows have been demonstrated promising: 800 nm (NIR-I, 650-950 nm) [9,10]; 1300 nm (NIR-II, 1000-1350 nm) [5,7,11,12]; 1700 nm (NIR-III, 1600-1840 nm) [6,[13][14][15][16][17][18][19], and 2200 nm window (NIR-IV, 2100-2300 nm) [20][21][22], including both excitation and emission. Zhang et al presented quantum dots emitting at $1600 nm, allowing 1-photon confocal fluorescence imaging of cutaneous blood vessels to a depth of 1200 μm under 808 nm excitation [23].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al developed NIR-II AIE DCTBT at 1700 nm excitation for twophoton fluorescence imaging depths of 2180 and 1135 μm in mouse brain with removed and intact skull, respectively [26]. Recently, we have demonstrated that 2200 nm is the last and longest window suitable for deep tissue MPM [20][21][22]. However, quantum dots with potential biological toxicity were used in fluorescence imaging excited at this window.…”
Section: Introductionmentioning
confidence: 99%
“…The other popular technique to obtain ultrashort pulses at 1700 nm excitation window is Raman soliton lasers taking advantage of the soliton self-frequency shift (SSFS) [10][11][12][13][14][15][16][17][18]. The soliton pulses propagating in optical fibers are affected by stimulated Raman scattering (SRS), causing energy to continuously transfer from the shorter wavelength to the longer wavelength, resulting in the SSFS.…”
Section: Introductionmentioning
confidence: 99%